Introduction. Humanitas and Humanities in the Contemporary World - Rebuffo, Cristina; Sisto, Davide (ETHICS IN PROGRESS, 2019)
From 12th to 16th September 2017 the 10th edition of the CeSPeC’s Summer School took place in Cuneo (Italy). This event revolved around the role of the humanities in the contemporary world and had the purpose of explaining the various perspectives which may demonstrate how still the contribution of such disciplines is important to interpret the world and the reality in the post-modern, global and post-digital era. In this introduction we provide a focus on the main topic and a brief presentation of the reflections composing the present papers collection.